Optical simulation and geometrical optimization of P3HT/GaAs nanowire hybrid solar cells for maximal photocurrent generation via enhanced light absorption. (December 2019) - Prashant, D.V.; Samajdar, D.P.; Sharma, Dheeraj
Highlights: GaAs nanowires are combined with conformal coating of P3HT for enhancing light. harvesting capability. Parametric Optimization is done using 3D finite-difference time-domain (FDTD) method. Maximum short circuit current density (Jsc) of 41.01 mA/cm 2 is achievable with the proposed structure. The proposed structure yields PCE of 27.85% which is 10% higher than its planar counterpart. Abstract: The implications of using the combination of inorganic and organic materials in the active layer of solar cells have motivated researchers to find a new pathway for flexible, low cost, and highly efficient future generation solar cells. III-V material based nanowires (NWs) with subwavelength scale diameters have shown excellent light harvesting and charge transport properties and can be easily combined with organic polymer materials and thin substrates to design hybrid solar cells (HSCs). To obtain optimum design requirements for GaAs nanowire array (NWA) HSCs, an optical simulation of poly(3-hexylthiophene) P3HT/ GaAs (NWA) hybrid solar cell is investigated using finite-difference-time-domain (FDTD) method. In comparison to planar substrate, P3HT coated NWA have shown superior optical properties owing to its intrinsic anti-reflection, broad absorption spectra, and efficient excitation of resonance modes. A steady improvement in light absorption of P3HT/GaAs NWA HSCs is observed as the polymer coating thickness increased up to a certain limit and beyond which there is a significant degradation in the exciton generation. The geometrical parameters like diameter (D) of NW and filling ratio or periodicity are also optimized to achieve superior light absorption and maximum short circuit current density (Jsc ). Under AM1.5G illumination, maximum photocurrent obtained for optimized structure with conformal coating of P3HT is almost 12% and 15% higher than its fully infiltrated and uncoated counterparts respectively